2012
DOI: 10.1177/0961000611434998
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy, complicity and culture in the library and information science preservation agenda: Observations from Romania

Abstract: This paper argues that researchers involved in cultural heritage preservation need to adopt a more inclusive ethnographic research methodology that pays special attention to how power, class, and status shape the communities we study. Based on observations from field research in Ghimeş-Fǎget, Romania, we discuss why the Hungarian ethnic identity was chosen as the village's most visible representation although residents had many other identities from which to choose. We show how local efforts to preserve cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…, 2022), classification and representation (Arab-Rahmatipour et al. , 2018; Olson, 1998; Olson and Schlegl, 2013; Vela, 2018) and archival knowledge (Bhebhe and Ngoepe, 2021; Caswell, 2019; Dávila-Freire, 2020; Klimaszewski et al. , 2013; Williams, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022), classification and representation (Arab-Rahmatipour et al. , 2018; Olson, 1998; Olson and Schlegl, 2013; Vela, 2018) and archival knowledge (Bhebhe and Ngoepe, 2021; Caswell, 2019; Dávila-Freire, 2020; Klimaszewski et al. , 2013; Williams, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, such critical methodologies have been seen as particularly valuable for research attempting to address equity and inclusion (Barnett and Witenstein, 2020;Sabati, 2019;Thambinathan and Kinsella, 2021;Tuhiwai Smith, 2021;V asquez-Fern andez et al, 2018). Drawing from various methodologies, critical LIS research has addressed issues such as power hierarchies within academia (Hepworth et al, 2014;Hudson, 2017;Willson, 2018;Willson et al, 2020), race and diversity in LIS (Acevedo-Gil, 2019;Hudson, 2017;Warren, 2016;Winston, 2008), gender and sexuality (Kitzie et al, 2021;Olson, 2007;Wagner et al, 2022), classification and representation (Arab-Rahmatipour et al, 2018;Olson, 1998;Olson and Schlegl, 2013;Vela, 2018) and archival knowledge (Bhebhe and Ngoepe, 2021;Caswell, 2019;D avila-Freire, 2020;Klimaszewski et al, 2013;Williams, 2021). It should also be noted that while much existing research has been conducted with such groups as the differently abled (e.g.…”
Section: Rq3 a Possible Solution? Indigenous And Decolonization Resea...mentioning
confidence: 99%
“…A team of American librarians, anthropologists, and student researchers set out to study information flow and control in Romanian villages. Their excellent articles on the contested control of village information resources (Whipple and Nyce, 2007), elite control of communities through information usage (Closet-Crane et al, 2009), and the power dynamics of cultural heritage movements (Klimaszewski et al, 2012) bring great contextual flavour to the conversation around libraries, cultural heritage, and information needs in the international context. Such collaboration provides a great model for librarians seeking to effectively understand research and information needs.…”
Section: Ethnographic Methods In Library Researchmentioning
confidence: 99%
“…This is not to be seen as a simple process, however. Klimaszewski et al (2012) query how the appropriate "community" is identified and who should speak for it. They argue that the way that power within local groups shapes how they might view particular cultural artefacts needs to be fully understood.…”
Section: Models Of Participation and Community Involvementmentioning
confidence: 99%